Βιβλιοκρισία: A. Cameron - N. Gaul (eds.), Dialogues and Debates from Late Antiquity to Late Byzantium, Routledge, Oxford -New York 2017 - ΛΟΥΚΑΚΗ, Μαρίνα (Byzantina Symmeikta, 2020)
Βιβλιοκρισία: A. Cameron - N. Gaul (eds.), Dialogues and Debates from Late Antiquity to Late Byzantium, Routledge, Oxford -New York 2017